Effect of Boundary Condition on Numerical Study of UAV Composite Skin Panels Under Dynamic Impact Loading - Wiranto, Ilham Bagus; Saraswati, Sherly Octavia; Alfikri, Iqbal Reza; Chairunnisa, Chairunnisa; Megawanto, Fadli Cahya; Adhynugraha, Muhammad Ilham; Majid, Nur Cholis (Mekanika: Majalah Ilmiah Mekanika, 2024)
In this study, a dynamic impact loading using Finite Element Analyses (FEA) was applied to an Unmanned Aerial Vehicle (UAV) composite skin panel. Two types of boundary condition panels were investigated (Fixed and Pinned). The composite UAV skin panel consists of upper panel and stiffener which have a thickness of 3 mm and 2 mm, respectively. The material properties used in this study was referring to Hexcel W3G282-F593 technical data sheet. A hemispherical steel indenter with 70 mm diameter and 120 kg of mass was used to crush the panel with a velocity of 4.43 m/s. The finite element analyses were performed using dynamic explicit solver in ABAQUS 6.23. At the beginning of study, the mesh convergence study was conducted to choose the proper mesh for main analysis. The convergence study was simulated using 20 kg mass to shorten computational time. The mesh size of 10 mm was chosen for the main analysis due to convergent result and short computational time compared to others mesh size. The impact deformation, contact force-displacement plot, and contact force-time plot was used to show the differences of using those boundary condition. The results show that fixed and pinned boundary condition reaches its contact force peak with the value of 29.2 kN and 22.8 kN, respectively.